Various Sources and Mode of Burns: Descriptive Study - Ohary, Raman; Sengar, Shaily (International Journal of Clinical and Biomedical Research, 2017)
Background: The World Health Organization estimates that the lifetime incidence of severe burns is 1% and that more than 300,000 people die annually from fire-related burns worldwide. Thermal injury is one of the major causes of morbidity & mortality in surgical patients & their successful management remains a challenge to modern medicine. Aim: Study of various sources and mode of burn. Method: Total of 764 patients admitted to the surgical ward and burn unit were included in the study. On admission, preliminary inquiries were made regarding the demographic profile, cause, mode of burn injury, surface area, and depth of burns were noted. Result: In most of the burn patient, the cause of burn was flame (75.9%), followed by moist heat (17.27%) and electricity (6.67%). Maximum no. of burn cases the source of heat was chimney (42.28%), followed by the stove (15.18%), as the next most common source. In most of the patient were accidentally burnt (96.20%) among which the majority were females. Conclusion: The most common cause of burn injury was flame. In most burn patients, the source of heat was a chimney, and most of the burn injuries were accidental. Keywords: Burns; Source; Mode of injury.